2014
DOI: 10.1097/dcc.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Eye Tracking as a Debriefing Mechanism in the Simulated Setting Improves Patient Safety Practices

Abstract: Eye tracking offers a unique opportunity to provide students with objective data about their behaviors during simulation experiences, particularly related to safety practices that involve the comparison of patient stated data to an artifact such as an ID band. Despite the limitations of current eye tracking technology, there is significant potential for the use of this technology as a method for the study and evaluation of patient safety practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 20 publications
1
37
0
3
Order By: Relevance
“…While some studies have demonstrated an acquisition of a pattern of "expert" gaze with focused training on gaze patterns (Jardoska et al, 2012; E.A. Henneman et al, 2014), it would be highly informative to examine the effects of such training over a prolonged period of time to ascertain whether this represents a permanent shift due to the use of eyetracking as an educational tool. Furthermore, the patterns of vision seen in the search-related expertise employed for medical screening may differ significantly from the examination of images from which a pathologic diagnosis is expected.…”
Section: F L R 47mentioning
confidence: 99%
See 2 more Smart Citations
“…While some studies have demonstrated an acquisition of a pattern of "expert" gaze with focused training on gaze patterns (Jardoska et al, 2012; E.A. Henneman et al, 2014), it would be highly informative to examine the effects of such training over a prolonged period of time to ascertain whether this represents a permanent shift due to the use of eyetracking as an educational tool. Furthermore, the patterns of vision seen in the search-related expertise employed for medical screening may differ significantly from the examination of images from which a pathologic diagnosis is expected.…”
Section: F L R 47mentioning
confidence: 99%
“…In the field of medical learning, several studies involving all levels of medical professionals have used individual eye-tracking data for both training, and debriefing after simulations (Jarodska et al, 2012;Henneman et al, 2014). As a debriefing strategy for medical simulations, eye-tracking can offer useful | F L R 49 information about errors that cannot be readily observed or verbalized.…”
Section: Hand-eye and Procedural Expertisementioning
confidence: 99%
See 1 more Smart Citation
“…These data provide a unique perspective for the wearer as recall of visual attention is unpredictable. Playback of an expert video or the student's own video may be used to assist novices to a higher level of achievement such as in a study by Henneman et al (2014). Further study with a detailed debriefing of experts or a simulation using a speak-aloud technique in which participants talk audibly what they are thinking could add more information as to why the expert looked where they looked or to train novices for subsequent simulations.…”
Section: Discussionmentioning
confidence: 99%
“…Other thought-provoking focuses are the attentional effort [11] by Longman on switching tasks, perception and observation of landscapes [12] by Dupont and patient safety practice [13] by Henneman.…”
Section: Medical Investigationmentioning
confidence: 99%